PENGARUH BIMBINGAN KELOMPOK TERHADAP KEMATANGAN EMOSI SISWA TERISOLIR DI KELAS XI AK SMK MUHAMMADIYAH 2 PEKANBARU - Sundali, Hengki; Saam, Zulfan; Umari, Tri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The tittle of this reaserch is the effect of group counseling services towards student’s emotional maturity isolated. The aims of this study were : 1) To know the description of students’ emotional maturity isolated before the guidance group services, 2) To know the process of guidance group services towards students’ emotional maturity isolated, 3) To know the description of students’ emotional maturity isolated after group counseling services, 4) To know the differences of students’ emotional maturity isolated before and after giving groups counseling services, and 5) To know the effect of guidance group services towards students’ emotional maturity isolated.The subject of this research was twelve isolated students of class XI AK SMK Muhammadiyah 2 Pekanbaru. Saturated sampling technique is applied. Based on the result of data processing, the students’ emotional maturity isolated before givingguidance group services more than half in middle category and less than half in worse category, whereas after giving guidance group services more than half in the middle category and less than half in better category.From the calculation of t-test, tgreater than ttable (6,97 > 2,074) then the hypothesis is accepted. There is a significant difference of students’ emotional maturity isolated before and after givingguidance group services at the level of 5% error. Based on the calculation of correlation coefficients and determinant coefficient, then the contribution of guidance group services towards students’ emotional maturity isolated is amount to 69% whereas 31% influenced by other factors.Keywords: Guidance group, emotional maturity